A new species of the simulium (Simulium) crocinum species-group (diptera: Simuliidae) from Vietnam - Takaoka, Hiroyuki; Ya'cob, Zubaidah; Sofian-Azirun, Mohd; Chen, Chee Dhang; Low, Van Lun; Lau, Koon Weng; Pham, Xuan Da (Malaysian Society of Parasitology and Tropical Medicine, 2019)
A new black fly species, Simulium yukawai, is described on the basis of one female and its pupal exuviae from Vietnam. This new species is placed in the S. crocinum species-group of Simulium (Simulium) (Diptera: Simuliidae). It is characterized in the female by the paraproct covered with 48–50 distinct hairs on its ventral and lateral surfaces, and in the pupa by the frons and most of the thorax bare, gill with six dark filaments in three pairs closely arising from the base, of which the two outer filaments of the dorsal and middle pairs are much longer than other filaments, abdomen with distinct spine-combs on the dorsal surface of segments 7–9, and cocoon wall-pocket shaped, with a large anterolateral window on each side. Taxonomic notes are given to separate this new species from related species. This species is the fourth member of the S. crocinum species-group known from Vietnam. © 2019, Malaysian Society for Parasitology. All rights reserved.